Liver Transplantation in Recipients Receiving Renal Replacement Therapy: Outcomes Analysis and the Role of Intraoperative Hemodialysis. Issue 7 (22nd May 2014) - Agopian, V. G.; Dhillon, A.; Baber, J.; Kaldas, F. M.; Zarrinpar, A.; Farmer, D. G.; Petrowsky, H.; Xia, V.; Honda, H.; Gornbein, J.; Hiatt, J. R.; Busuttil, R. W.
<x xml:space="preserve">Abstract</x> The Model for End‐Stage Liver Disease (MELD) system has dramatically increased the number of recipients requiring pretransplant renal replacement therapy (RRT) prior to liver transplantation (LT). Factors affecting post‐LT outcomes and the need for intraoperative RRT (IORRT) were analyzed in 500 consecutive recipients receiving pretransplant RRT, including comparisons among recipients not receiving IORRT (No‐IORRT, n = 401), receiving planned IORRT (Pl‐IORRT, n = 70), and receiving emergent, unplanned RRT after LT initiation (Em‐IORRT, n = 29). Despite a median MELD of 39, overall 30‐day, 1‐, 3‐ and 5‐year survivals were 93%, 75%, 68% and 65%, respectively. Em‐IORRT recipients had significantly more intraoperative complications (arrhythmias, postreperfusion syndrome, coagulopathy) compared with both No‐IORRT and Pl‐IORRT and greater 30‐day graft loss (28% vs. 10%, p = 0.004) and need for retransplantation (24% vs. 10%, p = 0.099) compared with No‐IORRT. A risk score based on multivariate predictors of IORRT accurately identified recipients with chronic (sensitivity 84%, specificity 72%, concordance‐statistic [c‐statistic] 0.829) and acute (sensitivity 93%, specificity 61%, c‐statistic 0.776) liver failure requiring IORRT. In this largest experience of LT in recipients receiving RRT, we report excellent survival and propose a practical model that accurately identifies recipients who may benefit from IORRT. For this select group, timely initiation of IORRT reduces intraoperative complications and improves posttransplant outcomes.